An operational model to investigate contact sports injuries - Gissane, C.; White, J.; Kerr, K.; Jennings, D. (Medicine & Science in Sports & Exercise, 2001)
Purpose: A cyclical operational model is proposed to examine the interrelationship of a number of factors that are involved in sports injury epidemiology. In sports injury research, investigations often attempt to identify a unique risk factor that distinguishes an injured player. However, a wide variety of factors can contribute to a sports injury occurring, and an understanding of the cause of injury is important to advance knowledge. Methods: The proposed model identifies a healthy/fit player initially, although the player may exhibit a number of intrinsic risk factors for sports injury. Before exposure to extrinsic risk factors, there is the opportunity for implementation of prevention strategies by coaching personnel and the sports medicine team. These strategies might include, among others, appropriate warm-up, adequate hydration, wearing protective equipment, and prophylactic taping. Additionally, preventative screening could take place to assess the various intrinsic and extrinsic risk factors that could lead to sports injury. Discussion: Two examples of how the operational model relates to contact sports injury cases are presented. Participating in sport inevitably exposes the player to external risk factors that predispose toward injury. The treatment of the injured player aims to restore the player to preinjury playing status and to prevent the injury from becoming chronic. Conclusions: It is suggested that the application of this proposed cyclical model may lead to greater success in understanding the multifaceted nature of sports injuries and furthermore help minimize injury risk and support the rehabilitation of injured contact sports participants.